Endothelial cells release cardioprotective exosomes that may contribute to ischaemic preconditioning. Issue 1 (December 2018) - Davidson, Sean; Riquelme, Jaime; Zheng, Ying; Vicencio, Jose; Lavandero, Sergio; Yellon, Derek
Abstract Extracellular vesicles (EVs) such as exosomes are nano-sized vesicles that carry proteins and miRNAs and can transmit signals between cells. We hypothesized that exosomes from endothelial cells can transmit protective signals to cardiomyocytes. Co-culture of primary adult rat cardiomyocytes with normoxic HUVEC cells separated by a cell-impermeable membrane reduced the percentage of cardiomyocyte death following simulated ischaemia and reperfusion (sIR) from 80 ± 11% to 51 ± 4% (P < 0.05; N = 5). When EVs were removed from the HUVEC-conditioned medium it was no longer protective. Exosomes were purified from HUVEC-conditioned medium using differential centrifugation and characterized by nanoparticle tracking analysis, electron microscopy, and flow cytometry. Pre-incubation of cardiomyocytes with HUVEC exosomes reduced the percentage of cell death after sIR from 88 ± 4% to 55 ± 3% (P < 0.05; N = 3). This protection required ERK1/2 activity as it was prevented by inhibitors PD98059 and U0126. Ischaemic preconditioning caused about ~3-fold higher rate of exosome production from HUVEC and from isolated, perfused rat hearts. This increase resulted in significantly greater protection against sIR in cardiomyocytes. In conclusion, exosomes released from endothelial cells can confer resistance to sIR injury in cardiomyocytes via the activation of the ERK1/2 MAPK signalling pathway, and may contribute to IPC.